IL-4, IL-13 and IFN-γ -induced genes in highly purified human neutrophils. (April 2023) - Kummola, Laura; Salomaa, Tanja; Ortutay, Zsuzsanna; Savan, Ram; Young, Howard A.; Junttila, Ilkka S.
Highlights: In neutrophils, IL-4 is more potent inducer of Stat6 activation than IL-13. IFN-γ and IL-4/IL-13 regulate distinct gene expression in neutrophils. IL-4/IL-13 induced genes are linked to MHCII biosynthesis oxygen or LPS responses. IFN-γ-induced genes are related to intracellular infections. Subjecting neutrophils to IL-4 decreases their anaerobic glycolysis. Abstract: Interleukin (IL)-4 and IL-13 are related cytokines with well-known specific roles in type 2 immune response. However, their effects on neutrophils are not completely understood. For this, we studied human primary neutrophil responses to IL-4 and IL-13. Neutrophils are dose-dependently responsive to both IL-4 and IL-13 as indicated by signal transducer and activator of transcription 6 (STAT6) phosphorylation upon stimulation, with IL-4 being more potent inducer of STAT6. IL-4-, IL-13- and Interferon (IFN)-γ-stimulated gene expression in highly purified human neutrophils induced both overlapping and unique gene expression in highly purified human neutrophils. IL-4 and IL-13 specifically regulate several immune-related genes, including IL-10, tumor necrosis factor (TNF) and leukemia inhibitory factor (LIF), while type1 immune response-related IFN-γ induced gene expression related for example, to intracellular infections. In analysis of neutrophil metabolic responses, oxygen independent glycolysis was specifically regulated by IL-4, but not by IL-13 or IFN-γ, suggesting specific role for type I IL-4 receptor in this process. Our results provide a comprehensive analysis of IL-4, IL-13 and IFN-γ -induced gene expression in neutrophils while also addressing cytokine-mediated metabolic changes in neutrophils.